BIOLOGICAL THERAPY OF INFLAMMATORY BOWEL DISEASES (American Journal of Pedagogical and Educational Research, 2024)
The term "inflammatory bowel disease" (IBD) covers a broad group of diseases, including acute and chronic enteritis and colitis of known and unknown etiology. In the literature, in accordance with ICD-10, the term IBD is understood as a narrower group of diseases combined into the class of IBD of non-infectious etiology, including Crohn's disease (CD) of the small and large intestine and ulcerative colitis (UC).